2012
DOI: 10.1029/2012eo410001
|View full text |Cite
|
Sign up to set email alerts
|

An alternate approach to assessing climate risks

Abstract: U.S. federal agencies are now required to review the potential impacts of climate change on their assets and missions. Similar arrangements are also in place in the United Kingdom under reporting powers for key infrastructure providers (http://www.defra.gov.uk/environment/climate/sectors/reporting-authorities/reporting-authorities-reports/). These requirements reflect growing concern about climate resilience and the management of long‐lived assets. At one level, analyzing climate risks is a matter of due dilig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
112
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 197 publications
(113 citation statements)
references
References 14 publications
0
112
0
1
Order By: Relevance
“…Uncertainties do not need to be an obstacle; rather, they are themselves useful information about what we know and what we do not know. One way to deal with uncertainties is to explore the importance of different factors, or to carry out sensitivity tests (Brown and Wilby 2012). Furthermore, a range of statistical methods can be applied to study the quality of model results and the dependency of these results on the choices made in the model set-up.…”
Section: Uncertaintiesmentioning
confidence: 99%
“…Uncertainties do not need to be an obstacle; rather, they are themselves useful information about what we know and what we do not know. One way to deal with uncertainties is to explore the importance of different factors, or to carry out sensitivity tests (Brown and Wilby 2012). Furthermore, a range of statistical methods can be applied to study the quality of model results and the dependency of these results on the choices made in the model set-up.…”
Section: Uncertaintiesmentioning
confidence: 99%
“…Changes other that the ones currently projected by climate models are plausible, particularly at impacts relevant spatial scales. Therefore decision makers should use a variety of scenarios for their planning, and not restrict their analysis exclusively to model projected ranges of uncertainties (Risbey 1998;Brown and Wilby 2012).…”
Section: Discussionmentioning
confidence: 99%
“…They argue that this is a more inclusive way of assessing risks, including from climate variability and climate change, than using the outcome vulnerability approach adopted by the Intergovernmental Panel on Climate Change (IPCC). Brown and Wilby (2012) assess climate risks using a form of sensitivity analysis ('stresstesting') to determine what climate characteristics a water supply system serving a metropolitan area in Massachusetts might be most sensitive to/at risk from. First, they demonstrated that GCM projections underestimated the variability statistics (standard deviation and lag-one autocorrelation) of streamflow for a region of the northeast United States based on a widely used, bias-corrected and statistically downscaled source of GCM projections (Maurer et al 2007).…”
Section: Risk-based Assessments Of Climate Change Impacts and Adaptatmentioning
confidence: 99%